2009
DOI: 10.3354/meps07894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 induced seawater acidification on infaunal diversity and sediment nutrient fluxes

Abstract: A mesocosm experiment was conducted to quantify the effects of short-(2 wk) and longterm (20 wk) exposure to acidified seawater on the structure and diversity of macrofaunal and nematode assemblages in 2 different sediment types. The impact of acidified seawater on sediment nutrient fluxes was also determined. Using carbon dioxide (CO 2 ) gas, seawater was acidified to pH 7.3 (mimicking ocean acidification), 6.5 or 5.6 (mimicking leakage from a sub-seabed CO 2 store site). Control treatments were maintained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
92
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 55 publications
15
92
3
Order By: Relevance
“…Previous studies were focused either in predicting the effects of future pH reduction or investigating the biogeochemical outcomes of coastal pH decline on certain organisms' response/survival or merely on the processes ultimately determining CO 2 fate and impact in aquatic systems (e.g. Andersson et al, 2007;Kitidis et al, 2011;Widdicombe et al, 2009;Laverock et al, 2014). Marine systems however, constitute of specific features, more complex than simple chemical or thermodynamic equilibria which are necessary, nonetheless, for any calculation or prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were focused either in predicting the effects of future pH reduction or investigating the biogeochemical outcomes of coastal pH decline on certain organisms' response/survival or merely on the processes ultimately determining CO 2 fate and impact in aquatic systems (e.g. Andersson et al, 2007;Kitidis et al, 2011;Widdicombe et al, 2009;Laverock et al, 2014). Marine systems however, constitute of specific features, more complex than simple chemical or thermodynamic equilibria which are necessary, nonetheless, for any calculation or prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental mesocosm, acidification led to changes in nematode communities in sediments affected by burrowing urchins (Dashfield et al 2008). Another experiment proved that acidification had a significant impact on the structure and diversity of nematode communities, especially in sandy sediment nematofauna (Widdicombe et al 2009). On the other hand, a 56-day CO 2 enrichment in a coastal microcosm caused no significant differences in the abundance of total meiofauna (nematodes and harpacticoid copepods; Kurihara et al 2007).…”
Section: Response To Ocean Acidificationmentioning
confidence: 99%
“…Effects on reef builders, e.g., by carbonate dissolution and the decrease of calcification rate, also could change the quantity and grain size of sediments around coral reefs (ANDERSSON et al, 2007). WIDDICOMBE et al (2009) have already shown the impact of seawater acidification on macrofauna, mainly that in coarse sediments.…”
Section: Discussionmentioning
confidence: 99%